EVALUASI SISTEM INFORMASI AKUNTANSI PERSEDIAAN OBAT OBATAN PASIEN COVID 19 PADA RUMAH SAKIT MITRA MEDIKA TANJUNG MULIA - Esra Kembar Tua Hutasoit; Edison Sagala; Ivo Maelina Silitonga (Universitas Methodist Indonesia, 2023)
This study aims to analyze the Accounting Information System for Drug Inventory at Mitra Medika Tanjung Mulia Hospital. In this study, the author uses a descriptive technique, which is an analytical process that begins with collecting data, grouping the data and then compiling, analyzing and interpreting so that the actual picture of the problem under study is obtained. The technique of collecting data is through a documentation study, which is to obtain the necessary data from the hospital regarding the accounting information system for drug supplies. Based on research and discussion regarding the Evaluation of the Accounting Information System for Drug Inventory for Covid-19 Patients at Mitra Medika Tanjung Mulia Hospital, it shows that the accounting information system implemented has been implemented well and is able to assist leaders in making good decisions.